Planned conception in a hyper immunized rhesus-d negative mother by elective plasmapheresis (Mymensingh Medical Journal, 2008)
Mymensingh Med J. 2007 Jul;16(2 Suppl):S67-69The abstract of this article is available on the PubMed website